Plant-Mediated Rhizosphere Oxygenation in the Native Invasive Salt Marsh Grass Elymus athericus - Koop-Jakobsen, Ketil; Meier, Robert J.; Mueller, Peter (Frontiers in Plant Science, 2021)
In the last decades, the spread of Elymus athericus has caused significant changes to the plant community composition and ecosystem services of European marshes. The distribution of Elymus athericus was typically limited by soil conditions characteristic for high marshes, such as low flooding frequency and high soil aeration. However, recently the spread of Elymus athericus has begun to also include low-marsh environments. A high-marsh and a low-marsh ecotype of Elymus have been described, where the latter possess habitat‐specific phenotypic traits facilitating a better adaption for inhabiting low-marsh areas. In this study, planar optodes were applied to investigate plant-mediated sediment oxygenation in Elymus athericus, which is a characteristic trait for marsh plants inhabiting frequently flooded environments. Under waterlogged conditions, oxygen (O2) was translocated from aboveground sources to the roots, where it leaked out into the surrounding sediment generating oxic root zones below the sediment surface. Oxic root zones were clearly visible in the optode images, and no differences were found in the O2-leaking capacity between ecotypes. Concentration profiles measured perpendicular to the roots revealed that the radius of the oxic root zones ranged from 0.5 to 2.6 mm measured from the root surface to the bulk anoxic sediment. The variation of oxic root zones were monitored over three consecutive light-dark cycles (12 h/12 h). The O2 concentration of the oxic root zones were markedly reduced in darkness, yet, the sediment still remained oxic in the immediate vicinity of the roots. Increased stomatal conductance improving the access to atmospheric O2 as well as photosynthetically production of O2 are likely factors facilitating the improved rhizosphere oxygenation during light exposure of the aboveground biomass. Elymus athericus’ capacity to oxygenate its rhizosphere is an inheritable trait that may facilitate its spread into low-marsh areas. Furthermore, this trait makes Elymus athericus a highly competitive species in marshes facing the effects of accelerated sea-level rise, where waterlogged sediment conditions could become increasingly pronounced.